Influência do talco nas propriedades de composições tipo porcelanato - Maruchin, Simone (2007)
A industrial composition was utilized for comparison with compositions contaiining 4, 6,8 and 10% of talc, that was prepared to study the influence of this new material in a porcelainized gres composition. This study concerns talc due to the following reasons: Ponta Grossa and Castro are near to Campo Largo´s ceramics pole: the increasing use of this material in products of technological interest; and its increasing acceptance in the market. The importance of a more detailed study was made necessary because talc is a relatively cheap product and with large reserves in the state of Paraná. The study was carried out using different levels of talc purity and varying its proportion to values higher than the ones found in the literature, aiming a larger use of this product. Firstly, the raw materials were characterized according to the chemical and mineralogical compositon as well as the particles size. The compositions were defined by the mineralogical compositions. Every composition had its barbotin done, dried, the proof bodies were shaped and sintherized using different temperatures. Analyses of the shaped samples were carried out according to the proof bodies mechanical characterization. The advantage of using a larger percentage of talc in the porcelainizes gres compositions was assessed according to these results.